학교 밖 청소년의 진로장애가 자아존중감과 우울을 통해 스마트폰 중독에 미치는 영향 - 이래혁(RaeHyuck Lee); 이재경(Jaekyoung Lee) (한국콘텐츠학회 논문지, 21(9), 2021)
The purpose of this study was to provide implications for social work practice by examining the influence of career barrier on smart-phone addiction through self-esteem and depression among out-of-school adolescents. Using data from the Panel Survey of School Dropouts conducted by the National Youth Policy Institute, this study examined the research questions by analyzing the direct and indirect influences of career barrier on smart-phone addiction with the PROCESS macro method. First, the results of this study showed that out-of-school adolescents' career barrier statistically significantly increased smart-phone addiction. Also, out-of-school adolescents' depression mediated the influence of career barrier on smart-phone addiction, but out-of-school adolescents' self-esteem did not mediate the influence. However, out-of-school adolescents' self-esteem and depression dual-mediated the influence of career barrier on smart-phone addiction. The level of career barrier decreased the level of self-esteem, and in turn increased the level of depression, and finally increased the level of smart-phone addiction. Based on the findings, practical strategies to address the smart-phone addiction of out-of-school adolescents were discussed. 본 연구는 학교 밖 청소년의 진로장애가 자아존중감과 우울을 통해 스마트폰 중독에 미치는 영향을 분석하여 사회복지 실천 함의를 제공하려는 목적으로 수행되었다. 이러한 연구문제를 규명하기 위해 본 연구는 한국청소년정책연구원에서 구축해놓은 학업중단 청소년 패널 조사의 원자료 중 일부를 활용하여 PROCESS macro 분석 방법을 통해 진로장애가 스마트폰 중독에 미치는 직·간접적 영향을 검증하였다. 먼저, 분석을 통해 학교 밖 청소년의 진로장애는 스마트폰 중독을 유의미하게 증가시키는 것을 확인하였다. 또한 학교 밖 청소년의 우울은 진로장애가 스마트폰 중독에 미치는 영향을 매개하였으나 자아존중감은 매개하지 않는 것으로 나타났다. 하지만 학교 밖 청소년의 자아존중감과 우울은 진로장애가 스마트폰 중독에 미치는 영향을 이중매개하고 있었다. 즉, 진로장애는 자아존중감을 낮췄고, 낮아진 자아존중감은 우울을 증가시켰으며, 증가된 우울은 최종적으로 스마트폰 중독을 증가시켰다. 이상의 결과를 토대로 학교 밖 청소년의 스마트폰 중독에 개입하기 위한 다양한 실천적 방안에 대해 논의하였다.